2017
DOI: 10.1002/ecy.1798
|View full text |Cite
|
Sign up to set email alerts
|

Short‐range dispersal maintains a volatile marine metapopulation: the brown algaPostelsia palmaeformis

Abstract: The annual brown alga Postelsia palmaeformis is dependent for its survival on short-distance dispersal (SDD) where it is already established, as well as occasional long-distance colonization of novel sites. To quantify SDD, we transplanted Postelsia to sites lacking established plants within ≥10 m. The spatial distribution of the first naturally produced sporophyte generation was used to fit dispersal kernels in a hierarchical Bayesian framework. Mean dispersal distance within a year ranged from 0.16 to 0.50 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…But we also found that B. oleracea seedlings established and survived following sowing in a few continuously unoccupied sections. Indeed, several studies have used seed or spore sowing, showing that unoccupied patches are indeed habitable by the species of interest (Milden et al 2006, Belinchon et al 2017, Dorken et al 2017, Paine et al 2017. This suggests it may be difficult to determine metapopulation structure simply by looking at occupancy patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But we also found that B. oleracea seedlings established and survived following sowing in a few continuously unoccupied sections. Indeed, several studies have used seed or spore sowing, showing that unoccupied patches are indeed habitable by the species of interest (Milden et al 2006, Belinchon et al 2017, Dorken et al 2017, Paine et al 2017. This suggests it may be difficult to determine metapopulation structure simply by looking at occupancy patterns.…”
Section: Discussionmentioning
confidence: 99%
“…How the form of dispersal affects metapopulation dynamics can be examined using simulation models, which include dispersal as an explicit process. In such models of plant metapopulations, dispersal is characterized using field data (Paine et al 2017) or by mechanistic models that represent the dispersal process (Bohrer et al 2005, Winkler et al 2009, Crawford et al 2015, Castorani et al 2017, while others represent dispersal using simple mathematical functions (Groeneveld et al 2008). While no studies have modeled the effects of HMD compared to natural dispersal in plants, a few modeling studies have contrasted short distance dispersal and LDD, albeit on a wide variety of systems and plant types.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, these seem very unlikely in our case, given the lack of air bladders for C . zosteroides and the low survival of recruits, suggesting that these rare events may not be enough to recover entire extensions of their populations at short-time scales, as seen in other macroalgae species [ 62 ]. For our studied species, which inhabits in relatively stable habitats [ 37 ] and present slow population dynamics [ 26 ], short-dispersal could be a mechanism to maintain local populations over more competitive species.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, P. palmaeformis density was not correlated strongly with any environmental variable, indicating other processes may be important. P. palmaeformis is an annual species with short distance dispersal and a high population turnover rate, which means density responses may be more dependent upon recruitment variability in space and time mediated by seasonal and episodic wave‐related disturbances and cleared spaces in mussel beds (Blanchette, 1996; Dayton, 1973; Paine, 1988; Paine et al, 2017). Thus, in general, and consistent with hypothesis H 4 (responses would vary among taxa), aspects of each species' response were idiosyncratic while others tended to be similar (Table 1).…”
Section: Discussionmentioning
confidence: 99%